A regional model of the Danish housing market - Simon Juul Hviid (Danmarks Nationalbank, 2017)
We estimate a regional model of the prices of Danish single-family houses and show that submarkets are interconnected via relative prices, giving rise to a ripple effect. We find strong evidence of a ripple effect in the short run of the model, but less so in the long run. We extend the model to allow for heterogeneity in fundamental elasticities based on factors such as local supply constraints and demographic compositions. We find that house prices are more sensitive to developments in fundamental factors, such as the housing stock, income and user costs in e.g. the Copenhagen area. Additionally, we document that the ripple effect is stronger from Copenhagen to other parts of Denmark than it is in the opposite direction. – – Vi estimerer en regional model for priser på enfamiliehuse og viser, at delmarkederne er forbundet via de relative priser, hvilket giver anledning til en bølgeeffekt. Vi finder stærke tegn på en bølgeeffekt på kort sigt og i mindre grad på langt sigt. Vi udvider modellen til at tillade heterogenitet i grundlæggende elasticiteter baseret på fx lokale udbudsbegrænsninger og den demografiske sammensætning, og vi konstaterer, at boligpriserne er mere følsomme over for udviklingen i fundamentale faktorer, såsom boligmassen, indkomst og brugeromkostninger fx i og omkring København. Derudover dokumenterer vi, at bølgeeffekten er stærkere fra København til de øvrige dele af Danmark end i modsat retning.
Keywords: C22; G12; R31; 330; House-price dynamics; regional house prices; global VAR models